A comprehensive overview in improving corrosion resistance of Mg alloys: Enhancing protective coatings with plasma electrolytic oxidation and superhydrophobic coatings - Arash Fattah-alhosseini; Haniye Salimi; Minoo Karbasi (Journal of Magnesium and Alloys)
The corrosion resistance of magnesium alloys is a significant concern in industries seeking to use these materials for lightweight structures. Plasma electrolytic oxidation (PEO) is a process that forms a ceramic oxide film on Mg alloy surfaces, effectively enhancing their corrosion performance in the short term. In this regard, optimizing PEO process parameters is crucial for creating a stable oxide layer. An improved level of corrosion resistance is ensured by applying superhydrophobic coating (SHC) on top of the PEO layer to prevent moisture infiltration, creating air pockets on the surface. Various methods are employed to fabricate SHC on Mg alloys, including techniques like electrophoretic deposition (EPD), Hydrothermal (HT), dip, and spray coating. The synergistic combination of PEO and SHC coatings has demonstrated encouraging outcomes in enhancing the corrosion performance of Mg alloys. This study offers an extensive overview of recent progress in the preparation, characterization, and corrosion behavior of Mg alloys by employing PEO coatings and SHC treatment processes.